The hyper-real pornography of video games: the simulation of ecstasy - Antônio Loures, José (DAT Journal, 2021)
The article proposes to discuss pornography in video games in a scenario of hyper-reality. Thus, cases of images produced through games are presented that have reached a more than real level according to the concept developed by Jean Baudrillard. In this context, to debate how pornographic representations of video game characters migrated to our daily lives with Japanese pornographic comics through ahegao. And finally, to present and problematize the process of community creation of the character Bowsette: fanarts, comics, cosplay, modifications and pornographic productions